Deteksi Keragaman Virus Tungro dari Beberapa Daerah Endemis di Indonesia dengan Teknik PCR-RFLP - R. Heru Praptana; Y. B. Sumardiyono; Sedyo Hartono; I Nyoman Widiarta; Muhammad Muhsin (Universitas Gadjah Mada, 2009)
Tungro is one of rice disease caused by two different viruses (rice tungro virus=RTV) i.e. Rice tungro bacilliform virus (RTBV) and Rice tungro spherical virus (RTSV) that are transmitted only by green leafhopper. Tungro had become a serious problem in several rice productions centre in Indonesia. Various components of management effort have been applied but they were inefficient in preventing the tungro disease development. Resistance variety is the most efficient component to tungro disease management. Complexity interactions of tungro disease components are mayor constraint in tungro disease management. Detection of molecular variability in rice tungro virus from several endemic areas in Indonesia were conducted by using PCR-RFLP technique. Existence of RTBV and RTSV in the infected plants collected from several endemic areas were successfully detected by PCR. The RFLP analysis with restriction enzymes BstYI and HindIII showed that there were significant difference among the RTSV originated from Java, Bali and Sulawesi.